Pelatihan Pengukuran Antropometri dan Edukasi Alat Kontrasepsi Pada Kader di Desa Sapen Manisrenggo Klaten - Fatimah Sari; Febry Heldayasari P; Evy Ernawati; Fatya Nurul H; Yunri Merida; Yustina Ananti (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
Anthropometry (body size) is a direct way of assessing nutritional status, especially the energy and protein state of a person's body. Food consumption and health (presence of infection) are environmental factors that influence anthropometry. The aim of this training is to increase the knowledge and skills of cadres in anthropometric measurements and education on contraceptives. The method of implementing training and education uses counseling and the practice of anthropometric measurements using a baby mannequin phantom. The number of participants was 15 Sapen Manisrenggo Klaten Village cadres. Implementation of activities in the early stages: participants are given a pretest in the form of a knowledge questionnaire to see how far participants know anthropometry and contraceptives before being given material and training. Implementation stage: activity participants are given training on anthropometric measurements and PPT material on anthropometry and education on contraceptives. In the evaluation phase, a post test was carried out in the form of a questionnaire similar to the initial pre test, to find out the extent of the knowledge and understanding of the participants in taking part in anthropometric measurement training and contraceptive education. From the results of the pre-test of anthropometric measurement knowledge of the cadre participants before the anthropometric measurement training was carried out with good knowledge of 0% and poor knowledge of = 73, 33%. From the results of the post test, the knowledge of cadre participants after training in anthropometric measurements was carried out with good knowledge = 66.66% and poor knowledge of 6.66%. From the results of the pre-test, knowledge of contraceptive education participants with good knowledge was 0% and less knowledge was 53.33%. From the results of the post test the knowledge of contraceptive education participants with good knowledge was 46.66% and less knowledge was 13.33%.